OP0071 Adipokine Effects on Differentiation of Osteoporosis and Osteoarthritis Spongiosa-Derived Mesenchymal Stromal Cells. (15th July 2016) - Tsiklauri, L.; Werner, J.; Frommer, K.; Mueller-Ladner, U.; Rehart, S.; Wenisch, S.; Neumann, E.
Abstract : Background: Osteoporosis predominantly affects elderly people and is characterized by bone loss, increased fracture risk and reduced regeneration ability. Age-related bone loss and articular cartilage damage correlate with increased bone marrow fat infiltration. With respect to age and age-related osteoporosis, there is an inverse relationship between bone mass and bone marrow adiposity. Bone marrow adipose tissue is metabolically active: It releases proinflammatory (e.g. adipokines) and matrix-degrading proteins (e.g. matrix metalloproteinases, MMPs), which promote progressive bone loss observed in osteoporosis and osteoarthritis. Moreover, bone marrow adipocytes share the same precursor with osteoblasts, the mesenchymal stem cell (MSC). Adipocyte-derived factors might influence differentiation of bone marrow-derived MSCs into osteoblasts and adipocytes. However, information on interactions between adipose tissue-derived factors and MSC differentiation is limited. Objectives: To analyze the presence of adipokines (visfatin, resistin and leptin) in the bone marrow cavity and their effects on differentiation of MSCs. Methods: Spongiosa containing bone marrow from femoral heads of patients undergoing hip replacement after osteoporotic femoral neck fracture or osteoarthritis were collected. Primary spongiosa-derived mesenchymal stromal cells (hMSCs) as well as commercially obtained MSCs were cultured in adipogenic and osteogenic media 3 weeks with/without adipokines. mRNA expression of adipokines, bone marker genes, TIMPs and MMPs of stimulated hMSCs/MSCs and as well as of bone samples were evaluated by real time PCR. Results: Expression of visfatin was significantly increased in osteoporotic bone (n=14) compared to non-osteoporotic bone. Higher expression of leptin was also detectable in osteoporotic bone (n=13). The stimulation with visfatin of hMSC during adipogenic differentiation significantly increased MMP13-expression (e.g. d21: 72-fold) but not leptin and resistin. In osteogenic differentiated cells, a reduction of MMP2 by stimulation of all adipokines could be observed (n=3). In contrast to adipogenic differentiation of hMSC, visfatin led to reduced expression of MMP13 during osteogenic differentiation (e.g. d21: 55-fold). In addition, visfatin decreased TIMP1 (e.g. d21: 2.86-fold), TIMP2 (e.g. d21: 3.17-fold), and RunX2 (e.g. d21: 5.85-fold) production, whereas leptin and resistin showed no effect on these molecules. Conclusions: Visfatin and leptin levels were found to be increased in osteoporotic bone tissue. The altered MMP and TIMP production, mediated especially by visfatin, might therefore influence bone remodeling at the adipose tissue/bone interface. Moreover, high levels of leptin in the osteoporotic bone might enhance bone degradation. Although leptin had no local effect on MSCs differentiation in vitro, it may also modulate bone degradation by affecting other cell types such as inflammatory cells. Disclosure of Interest: None declared